Detection System Design for Cu Contaminated Water Based on Red Diode Laser and LDR (Light Dependent Resistor) Sensor - Rakhmadi, Frida Agung; Zahroh, Hikmahtuz (Proceeding International Conference on Science and Engineering, 2017)
The research on making detection system of Cu contaminated water based on red diode laser and LDR sensor has been done. The purpose of this research was to know the characteristic of LDR sensor, to make the detection system of Cu contaminated water, and to test the detection system of Cu contaminated water. This research was conducted in five phases: characterization of LDR sensor, making data acquisition system, processing and analyzing of train sample data, making detection system, and implementation of detection system on test sample. The result of LDR sensor characterization in this research showed transfer function V = 0,004I + 2,1861 with relation of input-output relation which was very strong (r = 0,99267); sensitivity was 0,004 volt/lux; repeatability was 99,015%, and saturation for the light intensity ? 500 lux. Meanwhile, the succes rate of detection implementation on Cu contaminated water was 97,5%.